ID 361 – Remission of ESES after functional hemispherotomy is associated with significant language development. Issue 3 (March 2016) - Gröppel, G.; Dorfer, C.; Dressler, A.; Mühlebner-Fahrngruber, A.; Porsche, B.; Hainfellner, J.A.; Czech, T.; Feucht, M.
Abstract : To study the effect of functional hemispherotomy on electrical status epilepticus during slow wave sleep (ESES) and language development. The source-population comprised prospectively collected data from patients with a history of at least 2 years after functional hemispherotomy. Study inclusion criteria were ascertained diagnosis of ESES prior to surgery and complete developmental follow-up data. A control group without ESES was drawn from the source population. Language Quotients (LQ) prior to surgery and at last follow-up were calculated. Hypotheses were: (1) Children with ESES have lower preoperative LQs than children without ESES; (2) Remission of ESES after surgery is associated with significant 'catch up' of the LQs. Nonparametric Wilcoxon and Chi-square tests were applied. 11 cases (five female) and 21 controls (eleven female) were included. Prior to surgery, children with ESES had significantly lower LQs compared with their controls ( p  = 0.015). The median follow-up after surgery was 6.0 years (±2.2; range 2–9 years). ESES remitted immediately after surgery in 90.9% of the patients. A significant increase in LQ was noticed in these children ( p  = 0.038). The results were independent of the side of surgery. Functional hemispherotomy may have beneficial effects on ESES and further language development.